Credit Cooperatives and Income Growth: Analyzing the Role of Financial Sustainability - Zhen Liu; Yumei Xie; Jinbi Yang; Doudou Zhu (Discrete Dynamics in Nature and Society)
Credit cooperatives not only promote the rural economy but also play an important role in providing effective and green financing. This paper aims to study the role of financial sustainability in the relationship between credit cooperation and income growth. The scale of the credit cooperatives and the financial sustainability were selected as two instrumental variables to mitigate the endogeneity of credit cooperative loans. Based on the data from 74 village-level surveys collected from Inner Mongolia, the credit effect and income increase impact of the credit cooperative scale and financial sustainability were analyzed by two-stage least-squares (2SLS) analysis. The study found that the scale of the credit cooperatives can positively affect credit cooperative loans to increase farmer income, with financial sustainability playing as a moderator; credit cooperatives will have a more significant income-increasing effect on villages with a better economic foundation or lower poverty rate but will have no significant effect on villages with a poor economic foundation or high poverty rate.